2015
DOI: 10.1080/02699931.2014.996530
|View full text |Cite
|
Sign up to set email alerts
|

Memory for positive, negative and neutral events in younger and older adults: Does emotion influence binding in event memory?

Abstract: When remembering an event, it is important to remember both the features of the event (e.g., a person and an action), and the connections among features (e.g., who performed which action). Emotion often enhances memory for stimulus features, but the relationship between emotion and the binding of features in memory is unclear. Younger and older adults attempted to remember events in which a person performed a negative, positive, or neutral action. Memory for the action was enhanced by emotion, but emotion did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…A prominent finding is the so-called "weapon focus," which refers to the phenomenon that attention and later memory is narrowed to the negative stimulus of a scene (i.e., the weapon) at the expense of peripheral details (e.g., Christianson & Loftus, 1990). In more recent research, this general pattern has been supported and elaborated, showing that the binding of the constituent features is enhanced for emotionally arousing objects both in terms of quantity and strength, whereas the binding of distinct object and background features is impaired (e.g., Earles, Kersten, Vernon, & Starkings, 2016;Kensinger, 2007;Mackay et al, 2004; for a review and an integrating theory, see Mather, 2007). However, as the quantity of stored features and their memory strength have never been concurrently measured in that line of research, it remains to be shown whether a similar trade-off between quantity and memory strength exists in the processing of emotional stimuli, a question that awaits future research.…”
Section: Discussionmentioning
confidence: 94%
“…A prominent finding is the so-called "weapon focus," which refers to the phenomenon that attention and later memory is narrowed to the negative stimulus of a scene (i.e., the weapon) at the expense of peripheral details (e.g., Christianson & Loftus, 1990). In more recent research, this general pattern has been supported and elaborated, showing that the binding of the constituent features is enhanced for emotionally arousing objects both in terms of quantity and strength, whereas the binding of distinct object and background features is impaired (e.g., Earles, Kersten, Vernon, & Starkings, 2016;Kensinger, 2007;Mackay et al, 2004; for a review and an integrating theory, see Mather, 2007). However, as the quantity of stored features and their memory strength have never been concurrently measured in that line of research, it remains to be shown whether a similar trade-off between quantity and memory strength exists in the processing of emotional stimuli, a question that awaits future research.…”
Section: Discussionmentioning
confidence: 94%
“…They explained this phenomenon in terms of the activation of the amygdala, which facilitates consolidation and long-term memory reinforcement. On a behavioral level, Earles, et al (2016) showed that negative events have higher recall rates than positive ones, while Kensinger and Schacter (2006) found that negative events were remembered more precisely and more accurately than positive ones. In such studies, where emotion was introduced through the items, authors have often proposed explanations in terms of attentional mechanisms: information with a high emotional content captures attention more effectively and is therefore remembered better than nonemotional information (Bower, 1981;Kensinger & Corkin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The growing number of DNA exonerations of innocent people who were convicted on the basis of false eyewitness testimony, however, suggests that eyewitnesses to actual crimes are not immune to influences of the false memory mechanisms documented in this research. Indeed, recent research by Earles, Kersten, Vernon, and Starkings (2016) suggests that emotional content may sometimes lead to increased rather than reduced likelihood of later falsely remembering having seen an action carried out by someone who had actually been seen doing something else. Moreover, a great deal of eyewitness testimony focuses not on emotional criminal acts but rather on ordinary types of actions (e.g., who was talking to whom) that take on added importance in the context of the legal system.…”
Section: Caveatsmentioning
confidence: 99%